ANALYSIS OF THE TERTIARY STUDENTS’ ENGLISH WRITING ERRORS; WHAT ERRORS ARE AND WHAT LEVELS ARE - Dedi Aprianto (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2022)
Writing, the language skill three, is a part of the productive skill of the four intergrated language skills. Error Analysis as the language learning approach to study about the problematic English written product. It is the mostly-complecated skill than the others. This current study aims at analyzing the grammatical errors made of and investigating the levels of English grammatical errors produced. This study was carried out by using a descriptive quantitative research method by using a test, a guided writing test by letting the students write the patterned texts by answering the questions given, as the instrument to obtain the data on the error types made and the levels of English grammatical errors produced. This study shows that the non-syntactical errors found are spellings (44%), punctuations (19%), Capitalizations LCL (14%), and the selection of words (23%). Whereas the syntactical errors are the use of articles (5.5%), parts of speech (8%), subject-verbs agreement (11%), using regular and Irregular verbs (8%), making phrases (9%), subjunctives (4.5%), reported speech (6%), compound sentences (15), complex sentences (16%), modal usages (7%), and using tenses (10%). There are three levels of English grammatical errors produced; basic grammar errors (43%), intermediate grammar errors (16%), and the intermediate grammar errors (41%).